ANALISIS KESTABILAN MODEL PENYEBARAN FLU BURUNG TERHADAP POPULASI UNGGAS - Syifaul Janan; Tuhfatul Janan; Fani Firmansyah; Didi Harlianto; Nicky Yongkimandalan (PT Innovative Academic Journals, 2025)
This research aims to analyze Avian Influenza spread model around the equilibrium point. The population discussed is the poultry population which consists of two sub-populations, namely susceptible and infective. The method used is literature study through reference books and scientific articles related to the models. Then, the mathematical model, equilibrium point, and model stability were calculated. The results of calculations were made into a simulation model using Matlab and Maple software. It was found that there was an Avian Influenza virus spread to the poultry population which was influenced by several factors, namely birth, natural death, death due to infection, and migration (movement).